The effect of unemployment insurance benefits on (self-)employment: Two sides of the same coin? - Sebastian Camarero Garcia; Michelle Hansch (Deutsche Bundesbank, 2021)
Although a meaningful percentage of firms are created out of unemployment and current active labor market policies in Europe often subsidize unemployed individuals to start their own businesses, little is known about the role of unemployment insurance (UI) generosity for selfemployment. By using Spanish administrative data including previously unavailable information on self-employment, we exploit a reform-driven exogenous cut in UI benefits to identify its causal effect on general employment and decompose it into the effects on self-employment and re-employment. Exploiting a discontinuity in the UI benefit schedule which changed as a result of the 2012 Spanish labor market reform, we estimate the causal reform effects on the extensive margin of (self-)employment and on unemployment duration. We find heterogeneous effects on the extensive margin: while the job-finding rate increases, the startup rate decreases. Over different time horizons, the negative effect on self-employment (35-50%) outweighs the positive effect on employment (5-33%). Our UI benefit duration elasticity estimates indicate that reduced UI benefits extend unemployment duration for individuals transitioning into self-employment but shorten unemployment for individuals finding re-employment. Due to the reform's unintended consequences for self-employment, its general employment effect is much smaller than claimed by analyses that focus only on employment.
Keywords: H75; J64; J65; J68; L26; 330; Social Insurance; Self-Employment; Spain; Unemployment Insurance